The Wisdom of Sundanese Intercultural Communication in Social Interaction with Javanese Ethnic Communities - Chalik, Alex Abdu; Arrianie, Lely; Sarofah, Riska (Nyimak: Journal of Communication, 2023)
This study aims to explain the forms of social interaction between the Sundanese and Javanese ethnicities that take place in the form of adaptation, cooperation, tolerance, competition, and conflict of intercultural communication wisdom. This research was conducted in Kabawetan District, Kepahiang Regency, Bengkulu Province. The novelties in the research include obtaining an overview and explanation of the history of the migration of the Sundanese to Sukasari Village, forms of social interaction between the Sundanese ethnic community and the Javanese ethnicity, and the implementation of Sundanese cultural wisdom in intercultural communication with the Javanese. This study uses a qualitative approach through in-depth interviews with informants to explore information about the wisdom of Sundanese intercultural communication in social interaction with the Javanese ethnic community. The technique of taking informants is done by using the snowball sampling technique according key informants who will recommend other sources.. The results showed that the intercultural communication wisdom of the Sundanese in social interaction with the Javanese ethnic community has been carried out well through babasan and paribasa owned by the Sundanese ethnic community within its cultural framework.Keywords: Social interaction, ethnicity, intercultural communication, local wisdom ABSTRAKPenelitian ini bertujuan untuk menjelaskan bentuk interaksi soial antara etnis Sunda dengan etnis Jawa yang berlangsung dalam bentuk adaptasi, kerjasama, toleransi, kompetisi dan konflik kearifan komunikasi antarbudaya. Penelitian ini dilakukan di Kecamatan Kabawetan, Kabupaten Kepahiang, Provinsi Bengkulu. Kebaruan dalam penelitian antara lain untuk memperoleh gambaran dan penjelasan tentang sejarah migrasi orang Sunda ke Desa Sukasari, bentuk-bentuk interaksi sosial komunitas etnis Sunda dengan etnis Jawa, dan implementasi kearifan budaya Sunda dalam komunikasi antarbudaya dengan etnis Jawa. Penelitian ini menggunakan metode pendekatan kualitatif melalui wawancara yang mendalam dengan informan untuk menggali informasi mengenai kearifan komunikasi antarbudaya Orang Sunda dalam interaksi sosial dengan komunitas etnis Jawa. Teknik pengambilan informan dilakukan dengan Teknik snowball sampling melalui beberapa narasumber kunci untuk merekomendasikan informan lainnya. Hasil penelitian menunjukkan bahwa kearifan komunikasi antarbudaya orang Sunda dalam interaksi sosial dengan komunitas etnis Jawa telah dijalankan dengan baik melalui babasan dan paribasa yang dimiliki oleh komunitas etnis Sunda dalam kerangka kebudayaannya.Kata Kunci: Interaksi sosial, etnis, komunikasi antarbudaya, kearifan local